Pyloric Atresia in a Neonate: Harbinger of clinical suspicion; A Case Report - Yadav, Kamal; Chandra Tudu, Harish; Madhavnarayan Totadri, Varsha; Kumar Mohanty, Subrat; Kumar Jena, Pradeep (Journal of Neonatal Surgery, 2025)
Pyloric atresia is an extremely rare congenital anomaly that typically presents in the neonatal period with symptoms of non-bilious vomiting, feed intolerance and upper abdominal distension. X ray abdomen and pelvis in a classical case shows a single gas bubble/single large stomach shadow in the abdomen. Differential diagnosis include supraampullary duodenal atresia, antral web and malrotation with midgut volvulus. Due to its rare occurrence, diagnosis requires a high index of suspicion. Isolated Pyloric atresia has a relatively good prognosis whereas Pyloric atresia associated with other congenital conditions such as epidermolysis bullosa (most commonly associated), multiple atresia syndrome and aplasia cutis congenita carries a more dire prognosis. Prompt diagnosis and surgical intervention are critical to prevent severe complications. Here we describe a three-day-old female neonate, who presented to us with history of feed intolerance and non bilious vomiting since birth. Upon evaluation the neonate was suspected to have pyloric atresia,. The patient underwent a pyloroplasty for membranous atresia (Type 1 pyloric atresia) and thereafter had an excellent postoperative recovery period. This Case report illustrates the clinical presentation, diagnostic findings, surgical management and reviews the literature available with respect to pyloric atresia, with the aim of highlighting the importance of early recognition and appropriate surgical treatment of one of the rare types of gastrointestinal atresia.